Pembuatan Hand sanitizer Alami Dengan Memanfaatkan Tumbuhan Daun Sirih (Piper betle Linn) dan Jeruk Nipis (Citrus aurantifolia s.) pada Ibu-ibu PKK di Desa Tanjung Berulak - Sunarno; Yenti, Silvia Reni; Fadli, Ahmad; Wisrayetti, Wisrayetti; Amri, Amun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Excessive use of hand sanitizers can cause negative side effects on the skin such as irritation. This is because hand sanitizers on the market are made from alcohol. Therefore, the effort that can be done is by making innovative hand sanitizer products that utilize natural ingredients. Community service activities carried out in Tanjung Berulak Village located in Kampar District, Kampar Regency, Riau Province aimed to provide knowledge about training in making natural hand sanitizers from betel leaves and lime. This activity aims to educate the people of Tanjung Berulak Village, especially PKK women so that they can make their own hand sanitizers at home by utilizing materials available in the surrounding environment such as betel leaves and lime with mixing method. The stages of activities carried out in this service program include the socialization stage, the demonstration stage for making hand sanitizers, and the discussion stage. The implementation of the activity of making natural hand sanitizers was demonstrated directly to PKK women in Tanjung Berulak Village. The number of participants who took part in the socialization was 20 PKK women from Tanjung Berulak Village. The results of the service show that the people of Tanjung Berulak Village are very enthusiastic about participating in the socialization of making hand sanitizers from betel leaf and lime and can practice it in their respective homes.